Blocking Tics in Gilles de la Tourette Syndrome - Kaczyńska, Justyna; Janik, Piotr (Frontiers in Neurology, 2021)
Introduction: Patients with Gilles de la Tourette syndrome (GTS) may experience blocking tics (BTs) defined as recurrent, brief cessations of motor acts. The aim of this study was to assess the prevalence, age of onset, and clinical correlates of BTs in GTS patients. Materials and Methods: We performed a one-time registration study in a cohort of 195 consecutive GTS patients aged 5–66 years (mean age: 15.0±9.2; 47 females, 24.1%). All patients were personally interviewed and examined. Results: At least one BT occurred at some point in the lifetime of 73 patients (37.4%) with a mean age of onset of 10.4±5.9 years. BTs occurred an average of 4.8±5.3 years after tic onset. The most common BT was cessation of walking (n=59, 80.8%), followed by speech (n=19, 26.0%), running (n=18, 24.7%), and writing (n=9, 12.3%). Most of the patients (n=52, 71.2%) reported cessation of only one activity. Clinical associations of BTs included more severe tics, overall greater number of tics, and, to a lesser extent, higher age at evaluation and comorbid obsessive-compulsive disorder. Conclusions: BTs represent complex tics, early and common symptoms of GTS, and are associated with a more severe form of GTS.